From rat pathophysiology to genomic medicine: an interview with Howard Jacob (The Company of Biologists, 2016)
Howard Jacob is best known for pioneering genomic sequencing of a patient to solve a mysterious pediatric case in 2010. With roots in pharmacology and cardiovascular disease, however, his career has largely been dedicated to dissecting the physiology and genetics of the rat to help understand complex human diseases. Howard was Director of the Human and Molecular Genetics Center at the Medical College of Wisconsin for 16 years, during which time he applied a combination of approaches, including quantitative genetics, integrative physiology and next-generation sequencing, in rat models to shed light on cardiovascular, metabolic and renal disorders. He was a key contributor to the genomic toolbox for rat research, and generated the first targeted-knockout rat models using zinc-finger-nuclease technology. He also contributed to sequencing of the rat genome and establishment of the Rat Genome Database. In this interview, Howard provides his perspectives on the past, present and future of rat-based translational research and explains why, despite his many successes as the leader of a rat group, he recently made the transition to clinical genomics.